SUMOtherapeutics for Ischemic Stroke - Paramesh Karandikar; Jakob V. E. Gerstl; Ari D. Kappel; Sae-Yeon Won; Daniel Dubinski; Monica Emili Garcia-Segura; Florian A. Gessler; Alfred Pokmeng See; Luca Peruzzotti-Jametti; Joshua D. Bernstock (MDPI AG, 2023)
The small, ubiquitin-like modifier (SUMO) is a post-translational modifier with a profound influence on several key biological processes, including the mammalian stress response. Of particular interest are its neuroprotective effects, first recognized in the 13-lined ground squirrel (Ictidomys tridecemlineatus), in the context of hibernation torpor. Although the full scope of the SUMO pathway is yet to be elucidated, observations of its importance in managing neuronal responses to ischemia, maintaining ion gradients, and the preconditioning of neural stem cells make it a promising therapeutic target for acute cerebral ischemia. Recent advances in high-throughput screening have enabled the identification of small molecules that can upregulate SUMOylation, some of which have been validated in pertinent preclinical models of cerebral ischemia. Accordingly, the present review aims to summarize current knowledge and highlight the translational potential of the SUMOylation pathway in brain ischemia.